Design and Testing of Fractal Antenna Parameters based on the Koch Curve for Reception of Digital Terrestrial Television Signals in the UHF Band (Law, State and Telecommunications Review, 2019)
Purpose ”“ In this research paper, the electrical and radiation characteristics of a proposed fractal antenna based on the Koch curve in the second iteration for reception of digital terrestrial television signals are designed and analyzed by laboratory tests.Methodology/approach/design ”“ The design is based on the concepts of fractal geometry and on a previously designed antenna, which is adapted to obtain a different frequency of operation; the designed antenna is constructed in three different ways, finally, they are tested in the lab using vector-network-analyzer, that allows to measure parameters, such as: VSWR, gain and radiation pattern.Findings ”“ The fractal antenna based on the Koch curve has the necessary characteristics to receive digital terrestrial television signals in the UHF band.